Bone tumors in children and adolescents in pediatric practice - Żybowska-Męczyńska, Monika; Pawłowski, Bartosz; Sienkiewicz, Michał; Zatłoka-Mazur, Dorota; Klimas, Filip; Rusiński, Kacper; Potoczek, Adriana; Pudełko, Iwona; Zięba, Zuzanna; Szczepanik, Natalia (Quality in Sport, 2025)
Bone cancers in children are uncommon, making up approximately 5,5 % of all pediatric cancers. Childhood cancers are characterized by rapid development, and any delay in diagnosis can lead to serious consequences and even be life-threatening. The most common malignant tumors in key practice are: osteosarcoma (OS) and Ewing sarcoma (EWS). OS and EWS in children and adolescents require integrated diagnostics and age-appropriate therapy to ensure the best possible treatment outcomes. In recent years, the survival rates of pediatric cancer patients have improved and, consequently, it is necessary to reduce the long-term, late effects of treatment in order to promote the reduction of the deterioration in quality of life caused by treatment and to ensure the best possible return to everyday life.